Conducting polypyrrole‐coated banana fiber composites: Preparation and characterization. Issue 4 (13th March 2013) - Merlini, Claudia; Ramôa, Sílvia D.A.S.; Barra, Guilherme M.O.
Abstract In this study, conducting banana fibers (BF) were obtained through in situ oxidative polymerization of pyrrole (Py) on the BF surface using ferric chloride hexahydratate (FeCl3·6H2O) as an oxidant. Suitable reaction conditions are outlined for the polymerization of Py: oxidant/monomer molar ratio, Py concentration and polymerization time of 2/1, 0.05 mol.L−1 and 30 min, respectively. Under these conditions, high‐quality conducting fibers containing polyPy and BF (PPy‐BF) were obtained with an electrical resistivity as low as 0.54 Ω.cm. The PPy‐BF was blended with different concentrations of polyurethane (PU) by mixing the two components in a vacuum chamber and then applying compression molding. The electrical resistivity of composites with 25 wt% of PPy‐BF was around 1.8 × 105 Ωcm, which is approximately 108 times lower than that found for pure PU. Moreover, PU/PPy‐BF composites exhibited higher mechanical properties than pure PU and PU/PPy, indicating that these conducting fibers can also be used as reinforcement for polymer matrices. The properties of the PPy‐BF obtained by the method described herein open interesting possibilities for novel applications of electrically conducting fibers, from smart sensors to new conducting fillers that can be incorporated into several polymer matrixes to develop conducting polymer composites with good mechanical properties.POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers